Antidepressant Interactions with the NMDA NR1-1b Subunit. (7th May 2008) - Raabe, Richard; Gentile, Lisa
Abstract : The targets for tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), and selective norepinephrine reuptake inhibitors (SNRIs) are known to be the serotonin and norepinephrine transport (reuptake) proteins which are embedded in presynaptic nerve terminals and function to bring these neurotransmitters from the synaptic cleft back into the presynaptic neuron. Using a combination of intrinsic and extrinsic fluorescence quenching, Stern-Volmer analysis, and protease protection assays, we have shown that therapeutics from each of these three classes of antidepressants bind to the extracellular S1S2 domain of the NR1-1b subunit of the NMDA receptor. These results are in agreement with recent work from our lab demonstrating the interaction of antidepressants with the S1S2 domain of the GluR2 subunit of the AMPA receptor, another member of the ionotropic glutamate receptor subfamily, as well as work from other labs, and continue the discussion of the involvement of ionotropic glutamate receptors in depression.